2015
DOI: 10.1016/j.scog.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual masking & schizophrenia

Abstract: Visual masking is a frequently used tool in schizophrenia research. Visual masking has a very high sensitivity and specificity and masking paradigms have been proven to be endophenotypes. Whereas masking is a powerful technique to study schizophrenia, the underlying mechanisms are discussed controversially. For example, for more than 25 years, masking deficits of schizophrenia patients were mainly attributed to a deficient magno-cellular system (M-system). Here, we show that there is very little evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 131 publications
4
17
0
Order By: Relevance
“…Schizophrenia is a serious psychiatric disorder that affects approximately ~1% of the population worldwide and causes positive symptoms, such as delusions and hallucinations, negative symptoms, including withdrawal from social interactions and daily life activities, cognitive impairments, and disorganization syndrome. Experimental studies of visual masking have reproducibly revealed an elevated threshold for the perception of masked visual stimuli in schizophrenia ( Butler et al 2003 ; Charles et al 2017 ; Dehaene et al 2003a ; Del Cul et al 2006 ; Green et al, 1999 , Green et al, 2011 ; Herzog et al 2004 ; Herzog and Brand 2015 ; Plomp et al 2013 ). For instance, in classical masking experiments in which the target-mask duration is manipulated, patients with schizophrenia typically need a longer delay between the two, compared to controls, to consciously perceive the target ( Charles et al 2017 ; Del Cul et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a serious psychiatric disorder that affects approximately ~1% of the population worldwide and causes positive symptoms, such as delusions and hallucinations, negative symptoms, including withdrawal from social interactions and daily life activities, cognitive impairments, and disorganization syndrome. Experimental studies of visual masking have reproducibly revealed an elevated threshold for the perception of masked visual stimuli in schizophrenia ( Butler et al 2003 ; Charles et al 2017 ; Dehaene et al 2003a ; Del Cul et al 2006 ; Green et al, 1999 , Green et al, 2011 ; Herzog et al 2004 ; Herzog and Brand 2015 ; Plomp et al 2013 ). For instance, in classical masking experiments in which the target-mask duration is manipulated, patients with schizophrenia typically need a longer delay between the two, compared to controls, to consciously perceive the target ( Charles et al 2017 ; Del Cul et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, abnormalities in these pathways may cause direct losses of the perception of stimuli at specific spatial or temporal frequencies. Nonetheless, there is a suggestion that an overall deficit of visual pathways may be more likely ( Herzog and Brand, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of smoking status, SCZ patients present impairments in visual information processing, including motion perception, perceptual organization, spatial localization, temporal prediction, eye tracking, color perception, and visual contrast sensitivity ( Yee et al, 1987 ; Shuwairi et al, 2002 ; Butler et al, 2008 ; Levy et al, 2010 ; Herzog and Brand, 2015 ; Martin et al, 2017 ). The results of studies that investigated changes in visual sensitivity in SCZ have been controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several candidate endophenotypes have been proposed for both schizophrenia and bipolar disorder (15,16). Endophenotypes based on visual processing are of particular relevance because of their excellent reproducibility, etiology-independence, and their contributions to higher cognitive impairments such as object recognition (17)(18)(19)(20). Visual backward masking (VBM) is such a candidate endophenotype for schizophrenia (21,22), especially the shine-through paradigm, which has a much higher sensitivity and specificity than most other perceptual and cognitive tasks (23).…”
Section: Introductionmentioning
confidence: 99%